Effect of music therapy combined with aerobic exercise on sleep quality among breast cancer patients undergoing chemotherapy after a radical mastectomy: a randomized controlled trial - Li Chang; Yan Wang; Jie Zhang; Wenqian Zhao; Xiaomei Li; Lei Yang (BMC, 2024)
Abstract Purpose We aimed to study the effect of music therapy combined with aerobic exercise on the sleep quality of patients undergoing chemotherapy after a radical mastectomy. Methods A randomized controlled trial was conducted at the Breast Disease Diagnosis and Treatment Center, Shaanxi Province Tumor Hospital, from July 2017 to June 2019. 110 female breast cancer patients who underwent a radical mastectomy were recruited and randomly allocated into an intervention group or a control group. The intervention group completed music therapy combined with aerobic exercise from the first to the sixth admission to the hospital for chemotherapy, while the control group received only routine nursing care. The sleep quality of these patients was measured using the Pittsburgh Sleep Quality Index (PSQI). A linear mixed model was used to adjust the PSQI of patients after controlling for other confounding factors. Results The mean sleep quality score of the breast cancer patients who received chemotherapy after a radical mastectomy (baseline) was 8.86 ± 2.34. The intervention group had a significantly lower mean global PSQI score than the control group from the first test to the third test, with an adjusted mean difference of -1.05 (95%CI: -1.86, -0.24; P = 0.01), -2.89 (95%CI: -3.70, -2.08; P < 0.001) and − 4.84 (95%CI: -5.65, -4.03; P < 0.001), respectively. A change in the global PSQI score from baseline for the intervention group was from 0.55 (95%CI: -0.24, 1.34; P = 0.171) at the first test to 2.75 (95%CI: 1.96, 3.53; P < 0.001) at the last test, and for the control group was from − 0.51 (95%CI: -1.31, 0.29; P = 0.213 at the first test to -2.10 (95%CI: -2.91, -1.30; P < 0.001) at the last test. Conclusions An intervention of music therapy combined with aerobic exercise can significantly improve the sleep quality of female breast cancer patients undergoing chemotherapy after a radical mastectomy, and this intervention continuously improves many aspects of sleep reactivity. Clinical trial registration This study was registered in the Chinese Clinical Trial Registry (ChiCTR2100042975, 02/02/2021).